PALM BIO-WASTE DERIVED ACTIVATED CARBON AS ELECTRODE MATERIAL FOR SOLID-STATE ELECTRIC DOUBLE LAYER CAPACITOR - RIDWAN TOBI, AYINLA (2019)
The conversion of palm waste to activated carbon as electrode material of electric double layer capacitor (EDLC) have been researched and reported in literature. However, the resulting activated carbon from each palm bio-waste possess unique and individual properties associated to its lignocellulose chemistry. In addition, due to the use of liquid electrolyte, most report in literature have identified electrolyte leakage as a major challenge in EDLC fabrication. With the expectation of a complementary effect, the aim of this research is to explore the unique lignocellulose chemistry of palm waste as a composite to improve the properties of the activated carbon produced. Polyvinyl gel was also synthesized as electrolyte to allow miniaturization and solve the problem of liquid electrolyte leakage.